2015
DOI: 10.1080/19443994.2013.837003
|View full text |Cite
|
Sign up to set email alerts
|

Successive advanced oxidation of pyridine by ultrasonic irradiation: effect of additives and kinetic study

Abstract: To cite this article: M.A. Elsayed (2015) Successive advanced oxidation of pyridine by ultrasonic irradiation: effect of additives and kinetic study, Desalination and Water Treatment, 53:1, 57-65, A B S T R A C TPyridine has received considerable attention from environmental scientists and engineers, due to its undesirable effect in the water environment. Pyridine contaminated wastewater presents a great threat on water resources safety. In this research, the degradation and advanced oxidation of pyridine in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Finally, according to the reported absorption maximum ( λ max ) of pyridine in the literature (250 and 262 nm), [28] the nitrile and carbonyl functional groups and also the lone pair of electrons of alkoxy through resonance and extending of conjugated systems can cause the π electron delocalization in the pyridine scaffold. So, the presence of these moieties can increase the bathochromic effect of the λ max of pyridine to the longer wavelengths.…”
Section: Resultsmentioning
confidence: 93%
“…Finally, according to the reported absorption maximum ( λ max ) of pyridine in the literature (250 and 262 nm), [28] the nitrile and carbonyl functional groups and also the lone pair of electrons of alkoxy through resonance and extending of conjugated systems can cause the π electron delocalization in the pyridine scaffold. So, the presence of these moieties can increase the bathochromic effect of the λ max of pyridine to the longer wavelengths.…”
Section: Resultsmentioning
confidence: 93%
“…This can produce a shock wave as a physical effect or even chemical bonding due to the O‐H radical's formation by water sonolysis. [ 91 ]…”
Section: Extraction Techniquesmentioning
confidence: 99%
“…This can produce a shock wave as a physical effect or even chemical bonding due to the O-H radical's formation by water sonolysis. [91] Bitumen, that is, the soluble organic matter, can be extracted from the oil shale due to the bubbles' cavitation subsidence, which stimulates the mass transfer of the liquid-solid phases within the media, as illustrated in Figure 4. Figure 4 shows the continuous-loop ultrasonic/ co-solvent extraction system in which shale samples are treated with acid and water prior to extraction with ultrasonic-assisted waves and different configurations of potential solvents.…”
Section: Ultrasonic Assisted Extractionmentioning
confidence: 99%
“…Several studies have been conducted to treat wastewater bearing pyridine and pyridine derivatives like ultrasound coupled with advanced oxidation [4] , batch and column adsorption [5] , biodegradation using enzymes [6] , photo-Fenton [7] and ozonation [8] etc. Biodegradation generally does not treat larger concentration of effluent efficiently and operation is complicated, very slow and there is also difficulty in handling secondary waste.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound assisted advanced oxidation method can considerably reduce the operation time and requirement of chemicals due to improved mass transfer and enhanced generation of radicals creating economically feasible oxidation processes. The earlier research based on removal of pyridine by Elsayed [4] using bath sonicator reported intensified degradation in the presence of oxidising agents such as hydrogen peroxide and Fenton reagent at irradiation power of 360 W and operating frequency of 40 ± 2 kHz. Literature analysis associated with 2-Picoline removal revealed that very few illustrations for removal from wastewater are seen and that too based on adsorption [9] and biodegradation [10] .…”
Section: Introductionmentioning
confidence: 99%